Extremity Soft-tissue Reconstruction With the Conjoined Latissimus Dorsi–Groin Flap - Satsuki Tachibana, MD; Shinichi Asamura, MD; Kazuhiro Hira, MD; Masatoshi Teraguchi, MD; Kentaro Ueda, MD; Shigeaki Inoue, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Extensive soft-tissue defects in the extremities pose a significant challenge in reconstructive surgery. The combined latissimus dorsi (LD) and groin flap technique, a method developed by Harii et al in 1981, has shown promise in treating such defects. The purpose of this study was to illustrate the technique and results of using combined LD and groin flaps to reconstruct extensive upper and lower extremity defects. We present 4 cases of extensive soft-tissue defects treated with the combined LD–groin flap. The report details the surgical approach, including patient positioning in the semisupine position, flap design, blood supply considerations, and operative results. Our study included patients ranging in age from 20 to 84 years who successfully underwent extremity reconstruction with operative times ranging from 4 to 12 hours and 50 minutes. Various vascular supplies were used based on the defect location in a consistent semisupine position. Cases included an 82-year-old man and an 84-year-old woman with lower extremity necrotizing fasciitis, a 24-year-old man with a complex upper extremity injury, and a 20-year-old man with a severe lower leg wound. Each demonstrated effective flap implementation and recovery with customized flap designs and microvascular anastomoses. The conjoined LD–groin flap technique is effective in treating severe extremity injuries, providing extensive coverage with manageable operative times. Its adaptability to long-axis defects and semisupine positioning contributes to its efficacy in complex reconstructions. With continued advances in microsurgery, this technique has the potential for wider application in reconstructive scenarios.